Chiaroscuri della ragione: Kant e la pace perpetua - Brezzi, Francesca (B@belonline, 2024)
From Kant’s themes of peace, still relevant today, but unfortunately not realized, the path of restorative justice, justice that rebuilds the social bond, is outlined in the face of Kant’s rigorism and pessimism.